DESIGN AND RELIABILITY ANALYSIS OF EIGHT-LEGGED JACKET STRUCTURE IN JAVA SEA - Pratama Putra (NIM : 15511004), Aji
An offshore structure is designed to accept loads in order the function as an offshore exploration and exploitation facility. Optimal design has to be done in order to achieve a sturdy and economical offshore structure. In offshore structure designing, there are standards that are generally used, in which one of them is API RP2A. this standard has two versions: WSD (2007) and LRFD (1993). In API RP2AÃ‚Â–LRFD, environment loads factor is derived from extreme sea condition in North Sea. This standard is presumed to be unsuitable for Indonesian seas, which relatively calm compared to North Sea. Reliability analysis is conducted on existing offshore platforms, with member stresses as the performance criteria, as an early study of wave loads factor. The studied structure is an offshore platform in Java Sea. A reliability analysis with Monte Carlo method is being conducted, with wave height as random variable of load and steel yield strength as random variable of capacity. The structure is first designed optimum based on API RP2AÃ‚Â–LRFD design criteria using inplace and seismic analysis, and then critical member(s) is/are selected. Reliability index is obtained by processing the unity check of critical member(s). A reliability index with high number is representing structure being conservative. From reliability analysis that have been conducted in this report, resulting reliability index () of 14.86 on critical member 106P-206P (pile), and reliability index of 7.53 on critical member 203L-1C3K (jacket bracing). From this high number reliability index, it is concluded that the application of wave loads factor of API RP2AÃ‚Â–LRFD for offshore platform in Indonesian seas in unsuitable.